Fasilitas Kuliner Di Pekanbaru Dengan Pendekatan Arsitektur Organik - Syarafina, Amalia; Aldy, Pedia; Rijal, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The culinary world needs to be balanced with the preservation of the culinary Nusantara. It is necessary for harmony between the human environment and the natural environment or better known as organic architecture. The Unity of Nature concept applied to the building design and expected to realize an integrated spatial planning between different functions and activities. The concept was also implemented in mass and the shape of the pattern. Through organic architecture design method, the result was covered zone, mass order, exterior, mass formation, interior, and structure. Different functions separated in different zone, and the mass order used linear pattern that connected all three functions. Mass formation obtained from the formation adapted to the natural environment in the site. The used of structural systems in all three functions were organized to create comfortable interior space.Keywords: Culinary facilities, Organic Architecture, Unity of Nature